Zwitterionic Polarization‐Engineering Covalent Organic Frameworks for Targeted Ferroptosis‐Synergistic Photothermal Immunotherapy - Jiarong Liang; Si Wang; Zhonghui Ma; Fei Kuang; Xiangkun Li; Zhilong Gong; Jinzhu Su; Zhiyi Wang (Advanced Healthcare Materials, 2026)
ABSTRACT Combining efficient photocatalytic activity with precise targeting is crucial for covalent organic framework (COF)‐based nanomedicines to remodel the immunosuppressive microenvironment and sensitize “cold” tumors to immunotherapy. Herein, we constructed two isomorphic frameworks featuring distinct electronic topologies: a zwitterionic squaric acid (SA) COF with inherent electrostatic asymmetry, and a charge‐neutral terephthaldehyde (TA) COF. The spatial divergence of ion centers in SA COF triggers intense molecular‐level ionic displacement polarization, creating a robust internal electric field. Such unique field‐effect regulation accelerates photogenerated charge separation for efficient superoxide anion production, enhances intersystem crossing for singlet oxygen generation, and promotes nonradiative energy relaxation for high‐performance photothermal conversion under dual‐wavelength irradiation. After PEGylation and iRGD modification, the formulated SA@PEG‐iRGD exhibits excellent physiological stability and active deep tumor penetration. With near‐infrared absorption, it enables high‐contrast photoacoustic imaging for guided dual‐wavelength (660/808 nm) phototherapy. This spatiotemporally controlled therapeutic cascade triggers lethal ferroptosis and precise photothermal ablation, potently activating immunogenic cell death. Combined with aPD‐L1 therapy, it eliminates primary tumors, produces abscopal effects, and establishes immune memory against recurrence and metastasis. This study highlights the value of electronic structure engineering in COF‐based precision nanomedicine.